Heterozygous missense variant of the proteasome subunit β-type 9 causes neonatal-onset autoinflammation and immunodeficiency - Nobuo Kanazawa (Nature Portfolio, 2021)
Genetic variants of proteasome subunit genes have been shown to associate with perturbed immune function. Here authors show that a heterozygous missense variant of the immunoproteasome subunit β-type 9 causes an autoinflammatory/immune deficiency syndrome in humans and in a mouse model.